Transcriptome and Metabolome Analysis Unveil Anthocyanin Metabolism in Pink and Red Testa of Peanut (Arachis hypogaea L.). (6th August 2021) - Xue, Qiqin; Zhang, Xiurong; Yang, Hui; Li, Huadong; Lv, Yuying; Zhang, Kun; Liu, Yongguang; Liu, Fengzhen; Wan, Yongshan
Abstract : Peanut ( Arachis hypogaea L.) is an important source of oil and food around the world, and the testa color affects its appearance and commercial value. However, few studies focused on the mechanism of pigment formation in peanut testa. In this study, cultivars Shanhua 15 with pink testa and Zhonghua 12 with red testa were used as materials to perform the combined analysis of transcriptome and metabolome. A total of 198 flavonoid metabolites were detected, among which petunidin 3-O-glucoside and cyanidin O-acetylhexoside in Zhonghua12 were 15.23 and 14.72 times higher than those of Shanhua 15 at the R7 stage, revealing the anthocyanins underlying the red testa. Transcriptome analysis showed that there were 6059 and 3153 differentially expressed genes between Shanhua 15 and Zhonghua 12 in different growth periods, respectively. These differentially expressed genes were significantly enriched in the flavonoid biosynthesis, biosynthesis of secondary metabolites, and metabolic pathways. Integrated analysis of transcriptome and metabolome indicated CHS gene ( arahy.CM90T6 ), F3 ′ H genes ( arahy. 8F7PE4 and arahy. K8H9R8 ), and DFR genes ( arahy. LDV9QN and arahy. X8EVF3 ) may be the key functional genes controlling the formation of pink and red testa in peanut. Transcription factors MYB ( arahy.A2IWKV, arahy.US2SKM, arahy.SJGE27, arahy.H8DJRL, and arahy.PR7AYB ), bHLH ( arahy.26781 N, arahy.HM1IVV, and arahy.MP3D3D ), and WD40 ( arahy.L6JJW9 ) in the biosynthetic pathway of anthocyanin were significantly upregulated in Zhonghua 12 which may be the key regulatory genes in testa pigment formation. This is a comprehensive analysis on flavonoid metabolites and related genes expression in peanut testa, providing reference for revealing the regulatory mechanism of pigment accumulation in peanut testa.